Ecotheology Islam: Teologi Konstruktif Atasi Krisis Lingkungan - Abdul Quddus (Ulumuna, 2012)
The earth inhabited by human now is facing global environmental crisis. To respond to and tackle the crisis, a new awareness to explore the principles of religion has emerged today, which was then called ecotheology, an integral environmental insight based on ethical-theological as well as ethical-anthropological dimensions. This paper is aimed at, on the one hand, exposing principles of Islamic ecotheology that are able to be guiding principles in managing the nature, and on the other hand, comparing them with the principles of modern environmental ethics of the environmentalist/ eco-thinkers. The author argues that there are three principles of Islamic ecotheology that are relevant as the basis of ethical management of nature now days, namely the principle of tawḥid (unity of all creation), the principle of āmanah-khalīfah (trustworthiness-moral leadership), and ākhirah (responsibility).